The analysis of an ammonia/water hybrid heat pump in the ethanol production process - Visagie, Pieter Johannes Jacobus (North-West University, 2008)
Ethanol is a renewable energy source that could decrease society's dependence on fossil fuels, while reducing greenhouse gas emissions. Producing ethanol on a small scale on South African farms could provide farmers with the capability of increasing their profits by reducing their input cost. Ethanol can be directly used as fuel and could supply alternative products to their market. This study evaluated the feasibility of using an ammonia/water hybrid heat pump in the ethanol production process. A model for the material and energy balance of a small scale ethanol plant was simulated, to obtain the requirements to which the hybrid heat pump had to adhere. A two stage hybrid heat pump (TSHHP) was then modelled. It is capable of operating at high temperatures and it has high temperature lift capabilities, which are suitable in the production of ethanol. The results from the model demonstrated that the TSHHP could operate at an average temperature lift of 106°C with a maximum temperature of heat delivery as high as 142°C and cooling as low as 9°C. Simultaneous heating and cooling demand in the ethanol production process can be met with the TSHHP. For the TSHHP model, 120 kW of heating and 65 kW of cooling is supplied while maintaining a COP of 2.1. The model accuracy was also verified against another simulation program. Implementation of the TSHHP into the ethanol plant was then discussed, as well as methods to optimize production by energy management. When compared to conventional heating and cooling systems, it was found that the TSHHP provides a more cost effective and energy efficient way of producing ethanol. The economic evaluation demonstrated that the installation cost of the TSHHP would only be 63% of the price of a conventional system. The main advantage is that the TSHHP uses only 38% of the energy used in a conventional system.
Thesis (M.Ing. (Mechanical Engineering))--North-West University, Potchefstroom Campus, 2009.
Keywords: Heat pump; Hybrid; Refrigerant; Zeotropic mixture; Ethanol plant